The Influence of Visual Merchandising, Store Atmosphere, and One Stop Shopping on Impulse Buying in Consumers of Oh! Some (KKV) Galaxy Mall Surabaya - Reni Vianggraini; Jojok Dwiridotjahjono (Universitas KH. Abdul Chalim Mojokerto, 2025)
The rapid growth of the modern retail sector in Indonesia encourages retailers to continuously innovate in developing effective strategies to face competition. This study examines the influence of visual merchandising, store atmosphere, and one-stop shopping on impulse buying among consumers of OH! SOME (KKV) Galaxy Mall Surabaya. This research is an associative research type using a quantitative approach. Determination of the number of samples using the Cochran formula and sampling using purposive sampling techniques. Data collection was carried out by questionnaire, and data analysis was conducted using multiple linear regression. The results of the research indicate that visual merchandising, store atmosphere, and one-stop shopping simultaneously or partially have a significant influence on impulse buying. This study serves as a reference for retail managers to design effective marketing strategies to enhance competitiveness and sales volume.